Efficiency Optimization of CRISPR/Cas9-Mediated Targeted Mutagenesis in Grape - Ren, Fengrui; Ren, Chong; Zhang, Zhan; Duan, Wei; Lecourieux, David; Li, Shaohua; Liang, Zhenchang (Frontiers in Plant Science, 2019)
he clustered regularly interspersed short palindromic repeats (CRISPR)/Cas system is an efficient targeted genome editing method in studying gene function and has been successfully applied in grape. However, the reports about the efficiency of CRISPR/Cas9-mediated targeted mutagenesis in plant are rare. In this study, three key parameters including the GC content of single guide RNA (sgRNA), the variety of the suspension cells used for transformation and the gene expression levels of SpCas9 in transgenic cell mass were surveyed to optimize the editing efficiency of CRISPR/Cas9 system in grapevines. Six GC contents of sgRNAs were designed to target exon sites of the Vitis vinifera phytoene desaturase (VvPDS) gene, and two varieties ‘Chardonnay’ and ‘41B’ suspension cells (SC) were used as the transgenic cell mass (CM). The results of T7EI and PCR/RE assays showed that the editing efficiency of CRISPR/Cas9 system increases proportionally with the GC content of sgRNAs. In this way, the 65% GC content sgRNA allowed the highest editing efficiency in both SCs. We also noticed that CRISPR/Cas9- mediated gene editing was more efficient in ‘41B’ SC than in ‘Chardonnay’ SC. In addition, a significantly relationship was observed between the editing efficiency and the expression of SpCas9 at the transcriptional level. Taken together, these results provided a potential optimization scheme in for the application use of CRISPR/Cas9 system in grape.